Co-innovation and Integration and Implementation Sciences: Measuring their research impact - examination of five New Zealand primary sector case studies. Issue 1 (1st January 2021) - Small, Bruce; Robson-Williams, Melissa; Payne, Penny; Turner, James A.; Robson-Williams, Roger; Horita, Akiko
ABSTRACT: The Primary Innovation programme investigated co-innovation to solve complex agricultural problems in five New Zealand primary sector projects. The projects engaged diverse stakeholders using a collaborative, integrative process to co-define problems, and co-create and implement solutions. Each project included a Reflexive Monitor, who facilitated group relationships, encouraged a systems perspective, and integration of multiple disciplinary and stakeholder knowledges. Reflexive Monitors also encouraged reflexive practice and adaptive project management, while helping the team pursue the project ambition for change. This paper, with respect to the five projects, seeks to address the following research question: Is co-innovation an effective research approach for achieving societal impact from innovations? To address this question, we describe attempts to operationalise and measure co-innovation through 1) five behavioural principles of co-innovation, 2) Reflexive Monitors' focus on each principle, and 3) the presence or absence of elements of the Integration and Implementation Sciences Framework (i2S) for enhancing research impact. We evaluate the relationship between these three process measures and project success, measured by outputs and two proxy impact measures: participants' subjective comparisons with the counterfactual and anticipated achievement of desired long-term impacts. Results indicated that the five principles of co-innovation and the presence or absence of elements defined in the i2S framework were positively related to the three success measures. This suggests validity of these measurement tools, and of using a co-innovation approach and/or systematic attention to the elements of the i2S framework to enhance the processes, outcomes and impacts of projects tackling complex real-world problems.